The Eukaryotic Translation Initiation Factor 4E Controls Lettuce Susceptibility to the Potyvirus Lettuce mosaic virus - Nicaise, Valérie (The American Society for Plant Biologists, 2003)
The eIF4E and eIF(iso)4E cDNAs from several genotypes of lettuce (Lactuca sativa) that are susceptible, tolerant, or resistant to infection by Lettuce mosaic virus (LMV; genus Potyvirus) were cloned and sequenced. Although Ls-eIF(iso)4E was monomorphic in sequence, three types of Ls-eIF4E differed by point sequence variations, and a short in-frame deletion in one of them. The amino acid variations specific to Ls-eIF4E(1) and Ls-eIF4E(2) were predicted to be located near the cap recognition pocket in a homology-based tridimensional protein model. In 19 lettuce genotypes, including two near-isogenic pairs, there was a strict correlation between these three allelic types and the presence or absence of the recessive LMV resistance genes mo1(1) and mo1(2). Ls-eIF4E(1) and mo1(1) cosegregated in the progeny of two separate crosses between susceptible genotypes and an mo1(1) genotype. Finally, transient ectopic expression of Ls-eIF4E restored systemic accumulation of a green fluorescent protein-tagged LMV in LMV-resistant mo1(2) plants and a recombinant LMV expressing Ls-eIF4E° from its genome, but not Ls-eIF4E(1) or Ls-eIF(iso)4E, accumulated and produced symptoms in mo1(1) or mo1(2) genotypes. Therefore, sequence correlation, tight genetic linkage, and functional complementation strongly suggest that eIF4E plays a role in the LMV cycle in lettuce and that mo1(1) and mo1(2) are alleles coding for forms of eIF4E unable or less effective to fulfill this role. More generally, the isoforms of eIF4E appear to be host factors involved in the cycle of potyviruses in plants, probably through a general mechanism yet to be clarified.